2020
DOI: 10.1021/acsapm.0c00225
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Access to SO3H-Grafted Porous Organic Polymers (POPs@H): Synthesis of Diarylbenzopyrans/Naphthopyrans and Triazoles by Heterogeneous Catalytic Cyclocondensation and Cycloaddition Reactions

Abstract: All the reagents employed were available from commercial sources and were used without further purification. Freshly distilled solvents were used for the synthesis. Column chromatography was performed using silica gel of 100-200μ mesh. 1 H and 13 C NMR spectra were recorded on JEOL-Lambda spectrometers. IR spectra were recorded on a Bruker Vector 22 FT-IR spectrometer. Melting points were measured using a JSGW melting point apparatus. High-resolution mass spectra (HRMS) were recorded on a Waters ESI-QTOF machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
1
6
0
1
Order By: Relevance
“…The IAST selectivity of C 2 H 2 /CO 2 on CNOP-6, calculated to be 2.29 at 298 K and 100 kPa in a 50%:50% fraction, is comparable to those of numerous porous materials like JXNU-15 (2.39), UPC-200­(Al)-F-BIM (2.25), and FJU-36 (2.8) . The C 2 H 2 /CO 2 selectivity of 2.29 surpassed those of numerous previously reported porous materials, including MeBPs (1.5–1.7), [Ca­(dtztp) 0.5 (DMA)]·2H 2 O (1.7), and [Ni­(dpip)]·2.5DMF·H 2 O (1.9) . This demonstrates the excellent C 2 H 2 adsorption uptake and good C 2 H 2 /CO 2 selectivity of CNOP-6, indicating its potential for separating C 2 H 2 /CO 2 .…”
supporting
confidence: 61%
See 3 more Smart Citations
“…The IAST selectivity of C 2 H 2 /CO 2 on CNOP-6, calculated to be 2.29 at 298 K and 100 kPa in a 50%:50% fraction, is comparable to those of numerous porous materials like JXNU-15 (2.39), UPC-200­(Al)-F-BIM (2.25), and FJU-36 (2.8) . The C 2 H 2 /CO 2 selectivity of 2.29 surpassed those of numerous previously reported porous materials, including MeBPs (1.5–1.7), [Ca­(dtztp) 0.5 (DMA)]·2H 2 O (1.7), and [Ni­(dpip)]·2.5DMF·H 2 O (1.9) . This demonstrates the excellent C 2 H 2 adsorption uptake and good C 2 H 2 /CO 2 selectivity of CNOP-6, indicating its potential for separating C 2 H 2 /CO 2 .…”
supporting
confidence: 61%
“…Moreover, CNOP-6 demonstrates an impressive C 2 H 2 adsorption performance of up to 114.9 and 80.2 cm 3 ·g –1 under 273 and 298 K at 100 kPa, respectively, equivalent to 5.13 and 3.58 mmol·g –1 . Notably, the C 2 H 2 uptake obtained with CNOP-6 at 298 K exceeds those of previously reported NOPs, as displayed in Table S1, like TpPa-NO 2 (63.73 cm 3 ·g –1 ), TFT-COF (39.4 cm 3 ·g –1 ), and MeBP (64.6 cm 3 ·g –1 ) . Except for its higher C 2 H 2 uptake, CNOP-6 also exhibits an exceptional CO 2 uptake of 55.4 cm 3 ·g –1 under ambient conditions, which is competitive with the previously reported NOPs, like CNOPs (46.5–53.4 cm 3 ·g –1 ) and NUSs (10.3–11.2 cm 3 ·g –1 ) .…”
mentioning
confidence: 46%
See 2 more Smart Citations
“…A wide variety of organic building blocks and a number of methodologies to synthesize POPs have been developed; some of the methodologies employed rely on the multistep synthesis and the use of heavy/transition metal-catalyzed reactions for polymerization, limiting their practical applications. , In our quest for the development of POPs in a cost-effective manner based on readily accessible starting compounds and facile synthetic transformations that preclude the use of metals, , we recently showed that the aldol condensation reaction can be diligently exploited for the construction of POPs . The polymers obtained by aldol condensation as the reaction for polymerization possess α,β-unsaturated carbonyl functionalities that can be exploited for the stabilization of Pd(0) nanoparticles similar to that of Pd(0) in tris­(dibenzylideneacetone)-dipalladium(0) (Pd 2 (dba) 3 ), a catalyst applicable to a number of organic transformations. , In an extension of our ongoing research that focuses on bottom-up development of POPs, we have expanded our initial investigations and designed and synthesized polymers ANT and NAP based on aldol condensation, cf.…”
Section: Introductionmentioning
confidence: 99%